Assessment of the prevalence and associated risk factors of pediatric hydrocephalus in diagnostic centers in Addis Ababa, Ethiopia - Blein Mulugeta; Girma Seyoum; Abebe Mekonnen; Elbet Ketema (BMC, 2022)
Abstract Background Hydrocephalus (HCP) is a common disorder of cerebral spinal fluid (CSF) physiology resulting in abnormal expansion of the cerebral ventricles. Infants commonly present with progressive macrocephaly whereas children older than 2 years generally present with signs and symptoms of intracranial hypertension. Neither qualitatively nor quantitatively are there adequate data to determine the prevalence and incidence of HCP in the developing world. HCP is a treatable condition that when left untreated, has fatal consequences. Objective The objective of this study was to assess the prevalence of pediatric HCP and associated risk factors in diagnostic centers in Addis Ababa, Ethiopia. Methods This study was conducted using a cross-sectional facility-based study design over a two-time period, i.e. a 2-year retrospective data collection from January 2018 to January 2020 included 1101 patients and a prospective data collection from May 2019 to February 2020 included 99 patients. Children aged 5 years and below who came to the selected diagnostic centers for MRI/CT examination were studied. The collected data were analyzed using binary logistic regression. Result The retrospective study included 639(58%) males and 462 (42%) females. The mean age calculated was 22.3 months. Infants aged younger than 24 months 753 (68.4%) were significantly associated with HCP development (P < 0.05). In the retrospective study, HCP etiologies; Aqueductal stenosis (17.9%), Neural Tube defects (NTDs) (35.7%), post-infectious (10.1%) were identified. In the prospective study, the gender and age distribution was 57(57.6%) males, 42 (42.4%) females, 60.6% infants aged younger than 24 months with a mean age of 24.9 months. Inadequate consumption of folic acid and development of HCP was found to be statistically significant (P < 0.05). In the prospective study, HCP etiologies; Aqueductal stenosis (26.1%), Neural Tube defects (26.08%), and post-infectious (8.69%) were identified. The 3 years prevalence of HCP calculated in both studies was 22% (223 per 1000 live births). Conclusion The results of this study suggest that the high prevalence of HCP was due to the high prevalence of aqueductal stenosis and neural tube defects; with a small contribution of post-infectious causes. The majority of infants who present with HCP were aged younger than 24 months.